TSH enhances neurite outgrowth - Mansoori, Maryam; Latif, Rauf; Morshed, Syed A.; Zaidi, Mone; Davies, Terry F. (Frontiers in Endocrinology, 2024)
Extra-thyroidal effects of TSH have been reported in various tissues expressing the TSH receptor (TSHR) including several areas of the brain. However, the influence of TSH on neuronal phenotypes has not been examined. Using a well-characterized human neuroblastoma cell line (SH-SY5Y) we have examined TSH signaling effects on the phenotype of these cells after their neuronal differentiation.Following an 18-day differentiation protocol we successfully re-differentiated the SH-SY5Y cells into ~100% neuronal cells as indicated by the development of extensive neurofilaments with SMI-31 expression. Furthermore, using absolute digital PCR we quantified TSHR mRNA, and also TSHR protein expression, in the re-differentiated cells and found that the neuronal cells expressed high quantities of both TSHR message and protein at baseline. Exposure to TSH induced primary, secondary, and tertiary neurite outgrowths which are essential for cell-cell communication. Quantitative analysis of neurites using ImageJ showed a dose-dependent increase in neurites. The addition of TSH up to 1mU/mL resulted in a ~2.5-fold increase in primary, and ~1.5-fold in secondary, and tertiary neurites. The lengths of the neurites remained unaffected with the dosage of TSH treatment. Furthermore, TSHR signaling in the differentiated cells resulted in enhanced generation of cAMP, pPI3K, pAKT, and pNFkB pathways and suppression of pMAPK suggesting an influence of these signals in driving neurite outgrowth. These data showed that the TSH/TSHR axis in neurons may contribute to enhanced neurite out-growth. The potential pathophysiological effects of TSH on the